A PNA-Mediated Clamping PCR for Routine Detection of KRAS Mutations in Colorectal Carcinoma. Issue 1 (January 2014) - Messa, Francesca; Tonissi, Federica; Millo, Enrico; Bracco, Enrico; Ungari, Silvana; Lattanzio, Laura; Merlano, Marco; Damonte, Gianluca; Lo Nigro, Cristiana
The detection of somatic mutations in a tumor represents a valuable tool for tumor characterization and provides the clinicians with information for setting up the most appropriate therapy. KRAS mutations in codons 12 and 13 are important biomarkers routinely analyzed in the clinic for the management of anti-EGFR treatment in colorectal carcinoma (CRC). Here we report a sensitive and inexpensive assay for KRAS mutations based on a PNA-mediated PCR clamping. The assay displays very high sensitivity (0.7%) and specificity (96.7%) when compared to traditional sequencing (SS) and pyrosequencing (PS), two of the most commonly and routinely used methods employed today by diagnostic laboratories. Furthermore, the PNA assay requires only basic and low-cost laboratory equipment, in contrast with all the most recent PCR-based technologies, which are highly sensitive but also much more expensive. Finally, despite the PNA assay does not allow for the definition of specific mutations, it is the cheapest and easiest screening method to firstly stratify wild-type and mutated patients, information that is strictly necessary to clinicians for the management of CRC and anti-EGFR treatment.